'At risk' waist-to-height ratio cut-off points recently adopted by NICE and US Department of Defense will unfairly penalize shorter adults. What is the solution?. Issue 1 (January 2023) - Nevill, Alan M.; Leahy, Guy D.; Mayhew, Jerry; Sandercock, Gavin R.H.; Myers, Tony; Duncan, Michael J.
Abstract: Objectives: To a) demonstrate that adopting 'at risk' waist-to-height ratio (WHTR) cut-off points, recently approved by National Institute for Health and Care Excellence (NICE) and the United States Department of Defense (USDoD), will unfairly penalize shorter individuals and will be too lenient for taller individuals, b) to confirm that waist circumference (WC) of a sample of US service personnel, scales to approximately height 0.5, supporting the notion that WC, to be independent of height (HT), should be normalized using WC.HT −0.5 (WHT5R), and c) to identify the WHT5R cut-off points that will reduce or eliminate this unwanted bias. Subjects/methods: We employed a three independent cross-sectional sample design. All n = 58, 742 participants underwent anthropometric assessment of body mass, stature and waist circumference. Results: The allometric power-law model WC=a.HT^b for US service personnel identified the height exponent to be b= 0.418 (95 % CI 0.251–0.585), confirming that the simple body-shape index for WC to be independent of HT, should be WC.HT −0.5 . Chi-square tests of independence and for linear trend confirmed that by adopting WHTR cut-off point, shorter individuals (both service personnel and non-service participants) will be over penalized (classified as being 'at risk'). New WC independent-of-height ratio cut-off points were found to resolve this problem. Conclusions: Adopting WHTR cut-off thresholds (either 0.5 or 0.55) will lead to shorter adults being unfairly classified as being 'at risk' in terms of their central adiposity and general health status. Adopting new WHT5R cut-off point thresholds were found to greatly reduce or eliminate this bias.